1992
DOI: 10.1259/dmfr.21.1.1397450
|View full text |Cite
|
Sign up to set email alerts
|

Radiological survey of the cervical spine in cleft lip and palate.

Abstract: Cleft lip and palate is known to be associated with a number of other skeletal anomalies. The purpose of this study was to investigate the prevalence of possible malformations of the cervical spine and their relationship to velopharyngeal incompetence. The lateral cephalometric radiographs of 30 patients aged between 14 and 27 years of age with cleft lip and palate were compared with these of a control group, who had been involved in cycle accidents. The radiographs were assessed for morphological anomalies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 3 publications
4
18
3
Order By: Relevance
“…Also Kluemper et al [20] stated that facial morphology and respiratory mode are unrelated, and that cephalometric analyses should not be used in making clinical decision of nasal impairment. Nasopharyngeal depth has been reported to be shorter in cleft-affected subjects than in non-cleft individuals [21][22][23], although also deviant results have been presented [24]. It seems that since NASA and NASAR did not correlate with LARE they do not explain the /r/ distortion in cleft-affected subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Also Kluemper et al [20] stated that facial morphology and respiratory mode are unrelated, and that cephalometric analyses should not be used in making clinical decision of nasal impairment. Nasopharyngeal depth has been reported to be shorter in cleft-affected subjects than in non-cleft individuals [21][22][23], although also deviant results have been presented [24]. It seems that since NASA and NASAR did not correlate with LARE they do not explain the /r/ distortion in cleft-affected subjects.…”
Section: Discussionmentioning
confidence: 99%
“…13 Numerous studies have reported a higher prevalence of cervical spine anomalies in cleft lip and palate patients. 21,22 The prevalence of complete ponticulus posticus as reported in the literature is summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, craniofacial abnormalities are among the most common of all the birth defects. The most frequent of these are the CLP [7,13,19]. When investigating the craniofacial dysmorphology, it is tempting to make an association between two or more defects and link them to a common embryonic event.…”
Section: A B a Bmentioning
confidence: 99%